Konseling Spiritual Dalam Mengembangkan Disiplin Pekerja Doa Di Sekolah Menengah Guppi Palangka Raya: Spiritual Conselvation In Developing Discipline Of Prayer Workers In Guppi Palangka Raya Middle School - Lia Austina; Muhammad Andi Setiawan (Suluh: Jurnal Bimbingan dan Konseling, 2017)
The objectives of this study are: (1) To find out how the implementation of spiritual counselling at GUPPI Palangka Raya Middle School, (2) Knowing the forms of disciplinary worship in GUPPI Palangka Raya Middle School. While the method used by researchers to uncover the problem in this study is the case study method. Data collection is done using the method of observation, interviews, and documentation. The objects in this study are BK teachers, class teachers, PAI teachers, VII grade homerooms, Student Waka, students and principals. Based on the results of the investigation it was found that (1) spiritual counselling services had been going well in GUPPI Palangka Raya Middle School, but in its implementation there were still students who had not been disciplined in prayer worship, (2) forms of indiscipline conducted by GUPPI Palangka Raya Middle School students namely: slow, lazy, slacking down prayer times, irregular when praying, disorderly, engrossed in playing cellphones when the call to prayer reverberates, affected by friends who don't pray.